Wearing and sharing #wardrobechallenges: Finding inspiration when you have nothing to wear - Matthews, Rachel (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Since the emergence of the fashion blogosphere, sharing personal fashion choices and inspirations using hashtags such as #OOTD (outfit of the day) have become commonplace. The speed and volume of this content has grown exponentially, providing a mediated view of self-fashioning as well as a common trope of marketing communications adopted by influencers. Recently, there has been a noted change in wardrobe activities being shared on social media, that focus on the challenges fashion users have as they navigate their existing wardrobe. User-generated content (UGC) tagged with #wardrobechallenge draws together diverse posts ranging from how to re-wear wardrobe items through techniques such as the 30 wears challenge, struggles with closet decluttering and laundry tips. This type of wardrobe work is predominantly an activity undertaken in private; however, when shared and mediated through digital channels it offers greater visibility on the use phase of garments. Recognising that the use-stage holds much potential to extend the lifecycle of garments (Gwilt & Rissanen, 2012), this paper explores UGC to understand whether the sharing of wardrobe challenges holds potential to drive sustainable behaviour change. With many fashion users mistrustful or confused by what fashion brands say regarding sustainability and little evidence of industry engagement with the post-purchase phases of fashion – the study asks if #wardrobechallenge content offers an effective way of communicating sustainable fashion practices. This is a socio-material investigation, that draws on data from Instagram and TikTok tagged with #wardrobechallenge. A typology of wardrobe challenge practices has been developed; its classifications offer inspiration for ‘doing’ fashion beyond consumption and designations of the fashion industry. The study concludes by discussing how this form of UGC could build new ways of socialising and supporting sustainable behaviour change.